Observation of Microvascular Perfusion in the Hegu (LI4) Acupoint Area after Deqi Acupuncture at Quchi (LI11) Acupoint Using Speckle Laser Blood Flow Scanning Technology. (31st October 2012) - Huang, Tao; Yang, Li-Jian; Zhang, Wei-Bo; Jia, Shu-Yong; Tian, Yu-Ying; Wang, Guan-Jun; Mu, Xiang; Wang, Lu; Litscher, Gerhard
Abstract : The aim of this study was to investigate the traditional meridian theory using speckle laser blood flow scanning technology to observe microcirculation of the Hegu acupoint area after acupuncture stimulation on distant points. An observational study was conducted to observe the microvascular perfusion of Hegu (LI4) and control points after acupuncturing Quchi (LI11). Thirty healthy volunteers (mean age 31.6 ± 8.7 years) received deqi acupuncture on Quchi (LI11, right side), and simultaneously changes in microvascular perfusion of Sanjian (LI3), Hegu (LI4), Yangxi (LI5), and two control points were observed before, during, and after needling using a MOOR speckle laser. The results showed that the changes in microvascular perfusion of the observed points are not regular. After correction, the experiment showed that the blood perfusion on 3 meridian acupoints was increased while the perfusion on 2 control points was decreased following acupuncture stimulation, the changes at Hegu (LI4) being the statistically most significant ones. Deqi acupuncture can help in regulating the body's blood flow, with a certain degree of meridian specificity.